Pengaruh Ekspor dan Investasi Luar Negeri terhadap Pertumbuhan Ekonomi Berdasarkan PDRB Provinsi Jawa Barat Tahun 2015-2022 - Reza Septiana; Rayhan Ardiansyah; Syintia Pertiwi; Misfi Laili Rohmi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to describe how exports and foreign investment affect economic growth based on the GRDP of West Java province in 2015-2022. This research is a literature study that departs from quantitative methods using secondary data obtained from the Central Statistics Agency (BPS). This research uses a multiple linear regression approach with SPSS data processing tools. The results of the F test show that simultaneously, exports and foreign investment do not have a significant effect on GRDP in West Java province. Partially, both of them do not have a significant influence on GRDP. The findings of this research underline the importance of considering other factors that may influence the level of GRDP in West Java. The implications of these findings also provide a basis for further research that could explore additional factors that may influence the relationship between these three variables.